A Retrospective Analysis of the Most Frequently Root Canal Treated Tooth in Pediatric Patients Visiting a University Hospital In Chennai - Shruthi Manivannan1 , Geo Mani2 , Murugan Thamaraiselvan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: The aim of this study was to determine the most common permanent tooth which requires RCT inpatients below 18 years of age.Materials and methods: A retrospective cross sectional study of 581 subjects to determine the most commonpermanent tooth which requires RCT in patients below 18 years of age was carried out. The investigationwas done to relate the permanent tooth which requires an RCT to age and gender. Chi - square test was thestatistical test used for correlation in this study.Results: Among the 581 subjects, 238 were males (41%) and 343 were females (59%); Age 6-10 years(18.42%), Age 11-14 years (69.71%), Age 15-17 years (11.88%); Mandibular right first molar (25%); 11-14 years most common age group (p=0.063) that underwent RCT; Higher number girls underwent RCT(p=0.006).Conclusion: Thus based on analysis it was found that permanent mandibular right first molar is the mostcommon permanent tooth which requires RCT in patients below 18 years of age and there is a femalepredominance seen. Mandibular first molar was the most common permanent tooth that underwent RCT inthe study due to its high susceptibility to caries.Clinical significance: This study serves as a beneficial tool for the identification of common permanentteeth undergoing an RCT which in turn can lead to implementation of correct preventive strategies andawareness among dentists as well as the general population.